Event‐triggered finite‐time dynamic output feedback control for switched affine systems with asynchronous switching. Issue 2 (4th May 2022) - Chen, Yunjun; Mao, Xin; Zong, Guangdeng; Yang, Dong; Shi, Kaibo
Abstract: This paper investigates the event‐triggered finite‐time dynamic output feedback control for switched affine systems (SASs) with asynchronous switching. A key point of the study is to set up a dynamic output feedback switched affine controller together with an event‐triggered mechanism (ETM). By using an average dwell time (ADT) approach and resorting to a controller‐mode‐dependent Lyapunov functional, the finite‐time stability (FTS) performance is achieve for the closed‐loop SASs. The system dynamics under the proposed ETM are fully discussed during the synchronous and asynchronous switching intervals. The existence of the lower bound on interevent intervals is discussed emphatically, which excludes the occurrence of Zeno behavior. Finally, an application example of the DC‐DC converter is given to show effectiveness of the acquired control algorithm.